Indexing membership via responses to irony: Communication competence in Israeli radio call-in shows. (January 2018) - Livnat, Zohar; Dori-Hacohen, Gonen
Abstract: The aim of this paper is to theoretically associate the question of "membering" in call-in radio shows with the diverse responses of callers to these shows to hosts' ironic utterances. Assuming that reactions to irony depend in part on the speaker's communicative competence, we suggest that they might be indicative of the speaker's communicative competence in a specific speech community, such as that of radio call-in program. The indirectness of irony requires that speech be understood and interpreted in a way that is shared by the community. These elements are central to the definition of a speech community: "sharing rules for the conduct and interpretation of speech" (Hymes, 1974:54), and thus require an in-depth familiarity with this community's goals and agreements, modes of participation, and practices of speech. Highlights: Responses to irony are indicative of the speaker's communicative competence in a specific speech community. They index membership in the community of radio call-in program. Regular callers demonstrated that they were more skillful in responding to irony. These superior skills are due to their familiarity with the program.